Pengambilan keputusan yang tidak rasional sebagai akar perilaku konsumtif: tinjauan psikologi kognitif - Raffi, Muhammad Haidar (Maliki Interdisciplinary Journal, 2026)
Consumptive behavior is increasingly common among university students, especially in the digital era where trends, advertisements, and social comparison rapidly shape lifestyle choices. This article discusses how irrational decision-making may serve as the root of consumptive behavior from a cognitive psychology perspective. The decision-making process is often influenced by cognitive biases, heuristics, impulsivity, and low self-control. Cognitive psychology suggests that individuals do not always make decisions based on logical reasoning, but are frequently affected by emotional and cognitive distortions. This article outlines the psychological dynamics that drive irrationality in consumption as well as cognitive strategies that may enhance rational decision-making among students. Understanding these mechanisms is expected to help students manage consumptive behaviors and make more adaptive financial decisions.